Drug-associated infections and infestations in older adults with tumor necrosis factor-alpha inhibitors: a real-world retrospective and pharmacovigilance study - Yu, Xihui; Zhong, Jiahong; Zhuang, Xuemei; Lin, Zhuomiao; Fu, Hongbo; Zhang, Yaofeng (Frontiers in Pharmacology, 2025)
ObjectiveOne of the adverse events of greatest concern in patients receiving biologic therapies is the risk of infection, as infections are among the primary causes of premature mortality in this population, especially in the elderly. Because of the absence of head-to-head studies and limited duration and sample size of randomized controlled trials in the older adults, we analyzed the risk of infection associated with tumor necrosis factor (TNF) inhibitors by real-world adverse event analysis, seeking to identify medications with a reduced risk of infection and offering medication options for sensitive patients.MethodsA retrospective pharmacovigilance investigation was undertaken utilizing the FDA Adverse Event Reporting System (FAERS) database from the first quarter of 2010 to the fourth quarter of 2023. Drug-associated infections and infestations associated with TNF-α inhibitors (adalimumab, infliximab, etanercept, golimumab, and certolizumab pegol) were evaluated using a disproportionality analysis. The Reporting Odds Ratio (ROR) and Bayesian Confidence Propagation Neural Network (BCPNN) were utilized to detect AE signals.ResultsA total case of 3,239,508 cases were included after removing duplicates. Among the protective signals, etanercept showed the lowest IC025 value in septic shock (IC025 = −3.23). Notably, golimumab showed the highest IC025 value in tuberculosis (IC025 = 2.44). The five TNF-α inhibitors have high signals in mycobacterial infectious disorders. In the stratification analysis, golimumab was associated with a highest risk of infections and infestations in ankylosing spondylitis patients (ROR = 3.07, 95%CI = 2.70–3.50; IC = 1.26, 95%CI = −0.42–2.92). Univariate and multivariate logistic regression analysis indicated that gender, weight and medicine may be influencing factors for the AEs of infections and infestations (p < 0.05).ConclusionThe research highlighted that the difference in the risk of infection in the elderly who used TNF-α inhibitors between various TNF-α inhibitors, adverse events and therapeutic indications, respectively. The use of TNF-α inhibitors increased the infection risk in older adults. Etanercept exhibited the lowest infection risk, whereas certolizumab pegol manifested the highest risk in infections and infestations. Doctors need to pay close attention to the appearance of mycobacterial infectious disorders in older adults treating with TNF-α inhibitors, which displayed the strongest signal.